2012
DOI: 10.1128/jvi.05746-11
|View full text |Cite|
|
Sign up to set email alerts
|

The Human Cytomegalovirus Protein TRS1 Inhibits Autophagy via Its Interaction with Beclin 1

Abstract: Here we showed that the HCMV TRS1 protein blocks autophagosome biogenesis and that a TRS1 deletion mutant is defective in autophagy inhibition. TRS1 has previously been shown to neutralize the PKR antiviral effector molecule. Although phosphorylation of eIF2␣ by PKR has been described as a stimulatory signal to induce autophagy, the PKR-binding domain of TRS1 is dispensable to its inhibitory effect. Our results show that TRS1 interacts with Beclin 1 to inhibit autophagy. We mapped the interaction with Beclin 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
143
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 151 publications
(152 citation statements)
references
References 65 publications
7
143
2
Order By: Relevance
“…HCMV infection increased the levels of LC3B-II at 24 hpi, but these levels dropped at 72 hpi such that they were only slightly higher in the infected cells. This is consistent with prior work showing that HCMV transiently induces autophagy early in the infection (26)(27)(28). Incubation of cells with 100 mM trehalose from the beginning of the infection further increased LC3B-II levels in both the mock-infected and HCMVinfected cells at 24 and 72 hpi, with a greater increase observed in the infected cells.…”
Section: Trehalose Induces Autophagosome Formation In Infected Hffssupporting
confidence: 80%
See 1 more Smart Citation
“…HCMV infection increased the levels of LC3B-II at 24 hpi, but these levels dropped at 72 hpi such that they were only slightly higher in the infected cells. This is consistent with prior work showing that HCMV transiently induces autophagy early in the infection (26)(27)(28). Incubation of cells with 100 mM trehalose from the beginning of the infection further increased LC3B-II levels in both the mock-infected and HCMVinfected cells at 24 and 72 hpi, with a greater increase observed in the infected cells.…”
Section: Trehalose Induces Autophagosome Formation In Infected Hffssupporting
confidence: 80%
“…In fact, it appears that activation of autophagy occurs very early during HCMV infection of fibroblasts and does not require de novo protein synthesis since UV-irradiated virus induces autophagy (26). This induction appears to be transient, and at later times in the infection it has been reported that autophagy may be downregulated through the interaction of the viral gene product TRS1 with beclin-1 (27,28).…”
mentioning
confidence: 99%
“…1A) and the work of others (31) suggest that PHT cells are resistant to CMV infection, and studies of CMV-infected placentas suggest that CMV specifically targets invasive and endovascular cytotrophoblasts as a means of entry into the fetal compartment (31)(32)(33). CMV is known to inhibit host autophagosome biogenesis during its infection, even when autophagy is stimulated (34,35). However, the specific mechanism(s) underlying the up-regulation of CMV infection by C19MC miRNAs are likely complex, involving diverse viral and/or cellular strategies.…”
Section: Discussionmentioning
confidence: 99%
“…However, at later times of infection, coinciding with AC formation, HCMV blocks autophagy (Chaumorcel et al 2008) by a mechanism that requires de novo viral protein expression. One viral protein synthesized during this period is TRS1, which has been shown to block autophagosome biogenesis (Chaumorcel et al 2012). Interestingly, TRS1 has been shown to be present in the AC (Buchkovich et al 2009).…”
Section: Discussionmentioning
confidence: 99%